Interventional Treatment of Advanced Ischemic Heart Disease - Delgado, Reynolds. (Springer London, 2009)
Ischemic heart disease is one of the most important international public health problems. Population aging and steady improvements in the treatments available for acute coronary syndromes means that more people are now living longer with coronary artery disease (CAD). Therefore advanced ischemic heart disease, defined as heart disease caused by coronary atherosclerosis resulting in significant heart failure (HF), signs and symptoms of intractable angina, and thus severely limits on lifestyle or longevity, is becoming increasingly prevalent. Therapy is clearly challenging, but new advances are making effective therapy of these patients truly possible. Treatment of Advanced Ischemic Heart Disease, rather than looking at single specific disease states such as CAD or HF, focuses on the concept of the patient who has progressed to advanced states of ischemic heart disease. The Editors have assembled a group of expert contributors to assess the current guidelines and address the practical challenges of managing patients with advanced ischemic heart disease. The book also describes the basic mechanisms of the progression of HF due to CAD and assesses the therapeutic options available in this patient group. Treatment options and protocols are emphasized, making this an ideal practical reference for the practicing cardiology clinician and interventional cardiologist as well as the basic or clinical researcher and student of cardiovascular medicine.